CONVENTIONAL MINIMUM IN COPYRIGHT PROTECTION (THE BERNE CONVENTION) - J. Barg (International Journal of Medicine and Medical Research, 2018)
Background. Intellectual property rights are present in our everyday lives to a huge extent. Law of intellectual property is generally governed by national law, with general principles set out in international treaties. Copyrights strictly protect only the expression of ideas, not the underlying ideas, procedures, methods of operation, or mathematical concepts themselves. Berne Convention was first signed in 1886 and to this day is one of the most important international treaties concerning copyrights and moral rights.